HIV Case Management Support Service Is Associated with Improved CD4 Counts of Patients Receiving Care at the Antiretroviral Clinic of Pantang Hospital, Ghana. (20th September 2017) - Sarfo, Bismark; Vanderpuye, Naa Ashiley; Addison, Abigail; Nyasulu, Peter
Abstract : Background . Factors associated with individual patient-level management of HIV have received minimal attention in sub-Saharan Africa. This study determined the association between support services and cluster of differentiation 4 (CD4) counts among HIV patients attending ART clinic in Ghana. Methodology . This was a cross-sectional study involving adults with HIV recruited between 1 August 2014 and 31 January 2015. Data on support services were obtained through a closed-ended personal interview while the CD4 counts data were collected from their medical records. Data were entered into EpiData and analyzed using Stata software. Results . Of the 201 patients who participated in the study, 67% (129/191) received case management support service. Counseling about how to prevent the spread of HIV (crude odds ratio (cOR) (95% confidence interval (CI)) (2.79 (1.17–6.68)), mental health services (0.2 (0.04–1.00)), and case management support service (2.80 (1.34–5.82))) was associated with improved CD4 counts of 350 cells/mm 3 or more. After adjusting for counseling about how to prevent the spread of HIV and mental health services, case management support service was significantly associated with CD4 counts of 350 cells/mm 3 or more (aOR = 2.36 (CI = 1.01–5.49)). Conclusion . Case management support service for HIV patients receiving ART improves their CD4 counts above 350 cells/mm 3 . Incorporating HIV case management services in ART regimen should be a priority in sub-Saharan Africa.